Enhancing journalistic skills among teachers in Sleman Muhammadiyah Regional Leadership (PDM) - Sutipyo Ru'iya; Fajar Dwi Putra; Abdul Hopid; Yusron Masduki; Sutarman Sutarman; Sri Roviana; Hanif Cahyo Adi Kistoro; Yusutria Yusutria (Community Empowerment, 2024)
Writing proficiency demands continuous refinement to flourish. Consistent practice fosters an individual's writing skills. Various motivations drive writing, including enhancing an institution's popularity. Effective journalistic skills are crucial for public relations professionals to elevate an organization's public image. This community service initiative aimed to enhance the journalistic skills of teachers within the Sleman Muhammadiyah Regional Leadership (PDM) environment. The methodology employed involved journalistic training sessions. The training encompassed 67 participants and was conducted in the PDM Sleman meeting room, covering the fundamentals of journalism and effective writing strategies. The outcomes revealed a significant 58% improvement in journalistic knowledge among participants. This positive impact underscores the effectiveness of the training in enhancing participants' journalistic proficiency.